Comparative Preclinical Study of Lidocaine and Mepivacaine in Resilient Hyaluronic Acid Fillers - Romain Brusini; Julien Iehl; Elodie Clerc; Mélanie Gallet; François Bourdon; Jimmy Faivre (MDPI AG, 2022)
Background: Hyaluronic acid-based filler injections are now well-established aesthetic procedures for the correction of skin tissue defects and volume loss. Filler injections are becoming increasingly popular, with a growing number of injections performed each year. Although classified as a minimally invasive procedure, the introduction of a needle or a canula may remain painful for the patient. A major improvement was achieved with the incorporation of local anesthetics into the formulation for pain relief. Methods: In this study, two well-known anesthetics, lidocaine and mepivacaine, were systematically compared to assess their influence on filler mechanical and biological features. The impact of each anesthetic was monitored in terms of gel rheological properties, stability, durability, and degradation. The release profiles of each anesthetic were also recorded. Finally, the pharmacokinetics of each anesthetic in rats were assessed. Results: For all the rheological and biological experiments performed, lidocaine and mepivacaine influences were comparable. The addition of either anesthetic into a soft-tissue filler showed no significant modifications of the stability, durability, and degradability of the gel, with similar release profiles and pharmacokinetics at an equivalent concentration. Conclusions: Substituting lidocaine with mepivacaine does not impact the properties of the gels, and thus both can be equally incorporated as anesthetics in soft-tissue fillers.